Analisis Strategi Bersaing COWMAD - Warungnya Penggila Sapi - , Rahadi Saptata Abra ([Yogyakarta] : Universitas Gadjah Mada, 2011)
This research have two objectives that are to identify about management strategy orientation of COWMAD in order to reach COWMAD competitive strategy and identify about COWMAD competitive strategy based on strategy typologi of Miles and Snow. This research is a qualitative descriptive that be directed to evalueta about company strategy based on strategy management theory perspective. The data collected from observation and interview. The analysis is directed to explore strategy have been used and strategy development planning via SWOT analysis and competitive strategy typologi of Miles and Snow. As the result can concluded that (1) COWMAD has a strengthness on high customer trust that has been developed via communication and interraction with some potencial companies on institutions that related with restaurant service of COWMAD. The threatness come from other restaurants that prepare variety menu from beef processing, especially from competitors that geographically have same targets, that are consumers on Yogyakarta city area. (2) The differentiation strategy and overall cost leadership can be choosed as alternative competitive strategy for COWMAD. On this context, management can explore some unique aspects on product variation. While, overall cost leadership can be resulted based on synergy from food and beverage variety that sold on restaurant. (3) The prospektor can be choosed as strategy typologi that more suitable to explain competitive strategy of COWMAD. The main indication based on COWMAD orientation to differentiation strategy. As philosophy, differentiation strategy and prospektor strategy typologi have a similarity on orientation to become a uniqe company that differ with competitor.